CFD Simulation Verification Processes at Planing Hulls using An Interceptor - Budi Utomo; Samuel Samuel; Serliana Yulianti; Good Rindo; Muhammad Iqbal; Abubakar Fathuddiin (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2022)
Experimental test is one of the methods for predicting drag ships using towing tank. This method has a good level of accuracy but requires quite complex equipment and costs. With the advancing technology of computing, the CFD method has emerged as an alternative for problem-solving, especially in hydrodynamics analysis. This study aims to ensure the accuracy of Computational Fluid dynamics (CFD) by verifying experimental data on high-speed vessel using an interceptor. The Interceptor system generates a hydrodynamic lift force by intercepting the flow of water under the hull. Comparison of experimental results and numerical simulations will involve analysis of drag, heave and trim. Numerical simulations were carried out using ITTC recommendations as testing standards. This research uses the grid independence study method to ensure the accuracy of the mesh. CFD simulations were carried out using the overset mesh method and the k-epsilon to solve turbulence flow. The Dynamic Fluid Body Interaction (DFBI) module is employed to resolve the dynamic motion of the ship in order to assess hull movements based on by fluid forces and moments. There can be two degrees of freedom in the heave and pitch directions. All simulations are performed in calm water condition. Verification is carried out by reviewing the condition of the ship without an interceptor and with an interceptor. 100% stroke and 60% interceptor were used as variations of the verification of this study. The results of this study indicate that the CFD analysis has been verified by the experimental method with a maximum error range of 10.7%. Planing hull is a type of fast ship that has quite complex hydrodynamic characteristics. This study also shows that the use of interceptors is proven to improve the performance of the planing hull ship.